Assessment of the AHRQ Patient Safety Initiative Moving from Research to Practice Evaluation Report II (2003-2004) - Farley, Donna O. (RAND Corporation, 2007)
Updates the policy context of the Agency for Healthcare Research and Quality (AHRQ) patient safety initiative; documents the priorities and activities being undertaken; lays out an evaluation framework and possible measures of the effects on patient outcomes and on stakeholders other than patients. Discusses implications of the findings for future AHRQ policy, programming, and research; suggests ways to strengthen AHRQ activities.